The South China Sea disputes and law of the sea - Jayakumar, S.; Koh, Tommy T. B.; Beckman, Robert C. (NUS Centre for International Law series, 2014)
This book explores in detail the application of specific provisions of the UNCLOS and how the framework of international law applies to the South China Sea.